Sistem Pendukung Keputusan Penentuan Penerima Bantuan Langsung Tunai Dana Desa Dengan Metode Weight Product - Rudy Kurniawan; Tri Aristi Saputri (STMIK Pringsewu, 2023)
Assistance sourced from the Village Fund or more commonly known as the Village Fund BLT includes a type of cash grant to underprivileged residents sourced from village funds. Meanwhile, in Gantimulyo village, the handover of this assistance was given by two methods, namely through account transfers and direct giving. This assistance is intended for underprivileged citizens who have not received any assistance from the government. So far, data collection has been carried out by deliberation of each hamlet to determine the recipients of the assistance, but sometimes there are still errors. Among them, there are still recipients who have received other assistance and underprivileged residents have not been recorded. Therefore, it is necessary to make criteria to collect data to determine the recipients of the assistance program. This research was conducted to determine the decision-making method for determining the criteria for recipients of the BLT-DD program in Gantimulyo village, which later there are criteria that residents must have to be used as a reference so that social jealousy does not arise between community residents. So as to enable the beneficiaries to be effective, efficient and on target. This can be evidenced by none of the citizens protesting and getting more than one favor.